Philosophy of Astrophysics Stars, Simulations, and the Struggle to Determine What is Out There - Mills Boyd, Nora; De Baerdemaeker, Siska; Heng, Kevin; Matarese, Vera (Synthese Library, 2023)
This is an open access book. This book, the first edited collection of its kind, explores the recent emergence of philosophical research in astrophysics. It assembles a variety of original essays from scholars who are currently shaping this field, and it combines insightful overviews of the current state of play with novel, significant contributions. It therefore provides an ideal source for understanding the current debates in philosophy of astrophysics, and it offers new ideas for future cutting-edge research. The selection of essays offered in this book addresses methodological and metaphysical questions that target a wide range of topics, including dark matter, black holes, astrophysical observations and modelling. The book serves as the first standard resource in philosophy of astrophysics for all scholars who work in the field and want to expand or deepen their knowledge, but it also provides an accessible guide for all those philosophers and scientists who are interested in getting a first, basic understanding of the main issues in philosophy of astrophysics.